A self-powered deep-ultraviolet photodetector based on a hybrid organic-inorganic p-P3HT/n-Ga2O3 heterostructure. (1st July 2022) - Qi, Xiaohui; Ji, Xueqiang; Yue, Jianying; Li, Lei; Wang, Xia; Du, Ling; Liu, Zeng; Li, Peigang; Guo, Yufeng; Tang, Weihua
Abstract: A self-powered deep ultraviolet photodetector based on a hybrid Poly(3-hexylthiophene) (P3HT)/ β -gallium oxide-( β -Ga2 O3 ) heterojunction with planar structure is presented in this study. The P3HT precursor solution was spin-coating onto the Ga2 O3 film grown by metal-organic chemical vapor deposition (MOCVD). The prepared device demonstrates outstanding photoelectric performance with an ultra-low dark current of 0.18 pA, a high responsivity of 57.2 mA W −1, and a detectivity of 1.47 × 10 17 Jones under 1 μ W cm −2 at 0 V. Benefiting from the formation of the built-in electric field, the photocurrent and response speed have been improved. Furthermore, the physical mechanism of the device under self-powered mode was discussed through an energy band diagram. The device has good stability and repeatability under different light intensities and different voltages. This work provides a simple and effective strategy for designing self-powered ultraviolet photodetectors.